Regional Government Authority in Granting Building Approval Permits Under Indonesia’s Job Creation Law: Centralization, Digitalization, and Local Administrative Power - Arief Chaer Muzakir; Muhammad Chotib; Abu Nawas (UIN Jakarta, 2026)
This study examines the authority of regional governments in granting Building Approval Permits (Persetujuan Bangunan Gedung / PBG) under Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law. The study is motivated by the regulatory transformation from the former Building Construction Permit (Izin Mendirikan Bangunan / IMB) regime to the PBG system, which has significantly altered the distribution of authority between the central and regional governments within Indonesia’s decentralized governance framework. This research employs a normative legal research method using statutory and conceptual approaches. The analysis is based on primary, secondary, and tertiary legal materials examined qualitatively to evaluate the legal position and administrative authority of regional governments in implementing the PBG system under the current regulatory framework. The findings demonstrate that regional governments continue to hold a strategic role in the administration of building approvals, particularly in relation to technical assessments, supervision, and the implementation of norms, standards, procedures, and criteria established by the central government. Nevertheless, the Job Creation regulatory framework indicates a growing centralization of authority through the integration of digital licensing mechanisms, particularly the Online Single Submission (OSS) system, which has reduced the discretionary authority of regional governments in the licensing process. Furthermore, several implementation challenges remain evident, including limited human resources, inadequate technological infrastructure, and the lack of regulatory harmonization between central and regional authorities. This study concludes that the authority of regional governments in granting Building Approval Permits under Law Number 6 of 2023 remains legally recognized; however, such authority is primarily administrative and technical in nature within a more centralized regulatory structure. Therefore, strengthening institutional capacity, harmonizing regulations, and improving the integration of licensing systems are essential to achieving effective, efficient, and accountable public services in Indonesia’s building governance sector. Keywords: Regional government authority; Building Approval Permit (PBG); Job Creation Law; public administration; licensing system; decentralization; Online Single Submission (OSS); Indonesia.